Answers>Maths>IB>Article

Consider the functions f and g where f(x)=3x-5 and g(x)=x-2. (a) Find the inverse function for f. (b) Given that the inverse of g is x+2, find (g-1 o f)(x).

(a) In order to find the inverse of a function, it is easiest to swap x and y and solve for y. Here this would give, x=3y-5 => x+5=3y => (x+5)/3=y. Hence, f-1(x)=(x+5)/3. (b) Here it is important to remember the order in which to calculate the composition of a function and then slowly plugging in the required functions. This gives (g-1 o f)(x) = g-1(f(x))= g-1(3x-5)=3x-5+2=3x-3.

Answered by Rebecca M. Maths tutor

2387 Views

See similar Maths IB tutors

Related Maths IB answers

All answers ▸

Let Sn be the sum of the first n terms of the arithmetic series 2+4+6+... . Find (i) S4 ; (ii) S100 .


Given that sin(x) + cos(x) = 2/3, find cos(4x)


Write down the expansion of (cosx + isinx)^3. Hence, by using De Moivre's theorem, find cos3x in terms of powers of cosx.


What are the key elements to include in your Math assignment?


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences